2019
DOI: 10.1097/wco.0000000000000711
|View full text |Cite
|
Sign up to set email alerts
|

Pain in Parkinson's disease: new concepts in pathogenesis and treatment

Abstract: Purpose of reviewIn this review, we discuss the most recent evidence on mechanisms underlying pathological nociceptive processing in Parkinson's disease patients, as well as novel treatment strategies. Recent findingsIn Parkinson's disease, specific neurodegenerative changes may cause alterations in nociceptive processing at multiple levels. Optimization of dopaminergic therapies should always be the first step in the management of Parkinson's disease pain. Reportedly, rotigotine transdermal patch, a monoamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 96 publications
0
48
2
Order By: Relevance
“…The extensive heterogeneity of pain that is experienced in PD patients presents obstacles in identifying targets for treatment. Furthermore, a lack of controlled studies has left a dearth of evidenced based treatment recommendations, and current regimens are largely based on case reports and empirical evidence [83][84][85]. Nevertheless, an array of pharmacological and nonpharmacological treatment options is available to attempt to relieve the chronic pain symptoms of PD patients.…”
Section: Treatment Of Chronic Pain In Parkinson's Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…The extensive heterogeneity of pain that is experienced in PD patients presents obstacles in identifying targets for treatment. Furthermore, a lack of controlled studies has left a dearth of evidenced based treatment recommendations, and current regimens are largely based on case reports and empirical evidence [83][84][85]. Nevertheless, an array of pharmacological and nonpharmacological treatment options is available to attempt to relieve the chronic pain symptoms of PD patients.…”
Section: Treatment Of Chronic Pain In Parkinson's Diseasementioning
confidence: 99%
“…Monoamine oxidase inhibitors (MAOI-B), such as selegiline, may also be beneficial in treating PD related pain. A post-hoc analysis revealed that safinamide reduced the number of concomitant pain treatments that PD patients relied on, and also the scores of the "bodily discomfort" domain of the Parkinson's Disease Questionnaire-39 [84,94,95].…”
Section: Dopaminergic Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several syndromes are hypothesized to be involved in PD pain generation [10]. Generally, PD patients suffer from alterations in peripheral transmission, sensitive-discriminative processing, pain perception and pain interpretation in multiple levels, due to neurodegenerative changes in dopaminergic pathways, and non-dopaminergic pain-related structures [11].…”
Section: Introductionmentioning
confidence: 99%